Encompassing and rational expectations: how sequential corroboration can imply refutation. - Ericsson, N; Hendry, D (Federal Reserve Board (U.S.), 1989)
Even though pieces of empirical evidence individually may corroborate an economic theory, their joint existence may refute that same theory. We discuss examples concerning testing for omitted variables, simultaneity, and rational expectations in the context of general-to-simple versus simple-to-general modeling. The proposition in the first sentence strongly favors the building of empirical models which are consistent with all available evidence.